Segment Occlusion vs. Reconstruction—A Single Center Experience With Endovascular Strategies for Ruptured Vertebrobasilar Dissecting Aneurysms - Schob, Stefan; Becher, Anett; Bhogal, Pervinder; Richter, Cindy; Hartmann, Anna; Köhlert, Katharina; Arlt, Felix; Ziganshyna, Svitlana; Hoffmann, Karl-Titus; Nestler, Ulf; Meixensberger, Jürgen; Quäschling, Ulf (Frontiers in Neurology, 2019)
Objective: Ruptured dissecting aneurysms of the intracranial vertebral arteries exhibit a high risk for morbidity and mortality and are prone to re-rupture. Therefore, early treatment is mandatory to induce stagnation of the critically dynamic mural process. Endovascular approaches are occlusion and reconstruction, however, both carry specific risks and benefits. Most studies discuss only one of these approaches or focus on one specific device. Therefore, the study presents our experiences with both techniques, providing a considered algorithm on when to perform reconstruction or occlusion. Material&Methods: We reviewed 16 SAH-cases in our database, which were caused by ruptured dissecting V4 aneurysms and thereupon treated endovascularly. Clinical history, radiologic findings and outcomes were analyzed. Results: In 7 patients reconstruction was performed with 4 of them receiving stent-assisted coiling as primary strategy. One patient suffered early re-bleeding due to progression of the dissection. Thus treatment was augmented with implantation of 2 flow diverters. The remaining 2 patients were primarily treated with flow diverter telescoping. In 9 patients a deconstructive approach was followed: 6 patients received proximal V4 coil-occlusion, 3 patients received distal V4 coiling. 2 patients died (GOS 1) in the subacute stage due to sequelae of recurrent episodes of raised intracranial pressure and parenchymal hemorrhage. Two patients kept severe disability (GOS 3), six patients had moderate disability (GOS 4) and seven patients showed full recovery (GOS 5). None of the patients suffered from procedural or postprocedural ischemic stroke. Conclusions: In patients with good collateral vascularization, proximal or distal partial occlusion via coiling seems to yield the best risk-benefit ratio for treatment of ruptured dissecting V4 aneurysms, especially since no continued anticoagulation is required and possibly essential surgery remains feasible in this scenario. If possible, PICA occlusion should be avoided – although even proximal PICA occlusion can become necessary, when weighing against the risk of an otherwise untreated ruptured V4 dissecting aneurysm. Contrarily, if the dominant V4 segment is affected, the hemodynamic asymmetry prohibits occlusion and necessitates reconstruction of the respective segment. For this, implants with high metal coverage treating the entire affected segment appear to be the most promising approach.